A biocompatible cobaltporphyrin-based complex micelle constructed via supramolecular assembly for oxygen transfer. (24th March 2016) - Shen, Liangliang; Qu, Rui; Shi, Hejin; Huang, Fan; An, Yingli; Shi, Linqi
Abstract : Herein, a complex micelle as an oxygen nano-carrier is constructed through the hierarchical assembly of the diblock copolymer poly(ethylene glycol)- block -poly(l -lysine) (PEG- b -PLys), tetrakis(4-sulfonatophenyl)porphinato cobalt(ii ) (Co(ii )TPPS), a heptapeptide (Cys-His-His-His-His-His-His) and heptakis(2, 3, 6-tri-O-methyl)-β-cyclodextrin (TM-β-CD). Abstract : Herein, a complex micelle as an oxygen nano-carrier is constructed through the hierarchical assembly of the diblock copolymer poly(ethylene glycol)- block -poly(l -lysine) (PEG- b -PLys), tetrakis(4-sulfonatophenyl)porphinato cobalt(ii ) (Co(ii )TPPS), a heptapeptide (Cys-His-His-His-His-His-His) and heptakis(2, 3, 6-tri-O-methyl)-β-cyclodextrin (TM-β-CD). Co(ii )TPPS was encapsulated into the cavities of TM-β-CDs driven by the host–guest interaction so that the irreversible formation of a μ-oxo-dimer of Co(ii )TPPS can be effectively prevented. The imidazole groups of the heptapeptide were selected as good axial ligands coordinating to the centric cobalt of Co(ii )TPPS, which subtly constituted the five-coordinated precursor serving as an active functional centre for oxygen binding. The sixth position of Co(ii )TPPS can bind oxygen. Furthermore, the host–guest inclusion (TM-β-CD/Co(ii )TPPS) was loaded into the hydrophobic core of the complex micelle and tightly fixed with PLys chains. The hydrophilic PEG blocks stretched in the aqueous solution constitute the shells which stabilize the structure of the complex micelle as well as impart the complex micelle sufficient blood circulation time. Moreover, the complex micelle exhibited excellent biocompatibility and cellular uptake. Therefore, the rationally designed amphiphilic structure can work as promising artificial O2 carriers in vivo . Potentially, the complex micelle can be expected to change the anaerobic microenvironment and find applications in the repair of the cells damaged by cellular hypoxia.